Making a New Journey: Comparing the Settlement Experiences of Adult and Child Refugees in Atlantic Canada - Fang, Tony; Hartley, John; Khan, Shanawaz (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2025)
This article applies the ACL (Age at migration, Context/contact opportunities, and Life cycle stage) framework and uses qualitative interview data to compare the integration of Syrian adult and child refugees in St. John’s, Canada. Almost all children reported having Canadian-born friends, outpacing adults, facilitated by highly integrated classrooms. Their recreational activities were less structured. While adults focused on language school or settlement agency events, children were more open to new experiences and were more optimistic about Canadian weather and food. They more often walked or bused to school, with adults favouring automobiles for transportation.